4 . 3^2 - 75 : 5^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 7\(x\) - \(x\) = 521 : 519 + 3.22.7
6\(x\) = 53 + 3.4.7
6\(x\) = 125 + 12.7
6\(x\) = 125 + 84
6\(x\) = 209
\(x\) = 209 : 6
\(x\) = \(\dfrac{209}{6}\)
b; 11\(x\) - 7\(x\) + 34 : 33 = 54 + 2\(x\)
4\(x\) + 3 = 625 + 2\(x\)
4\(x\) - 2\(x\) = 625 - 3
2\(x\) = 622
\(x\) = 622 : 2
\(x\) = 311
c; 75 - 5.(\(x-3\))3 = 700
5.(\(x\) - 3)3 = 700 - 75
5.(\(x\) - 3)3 = - 625
(\(x\) - 30)3 = - 625 : 5
(\(x\) - 30)3 = - 125
(\(x-3\))3 = (-5)3
\(x\) - 3 = - 5
\(x\) = - 5 + 3
\(x\) = -2
d, 3.(2\(x\) - 1)2 = 75
(2\(x\) - 1)2 = 75 : 3
(2\(x\) - 1)2 = 25
\(\left[{}\begin{matrix}2x-1=-5\\2x-1=5\end{matrix}\right.\)
\(\left[{}\begin{matrix}2x=-5+1\\2x=5+1\end{matrix}\right.\)
\(\left[{}\begin{matrix}2x=-4\\2x=6\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=-2\\x=3\end{matrix}\right.\)
1) \(3\sqrt{2}-4\sqrt{18}+2\sqrt{32}-\sqrt{50}\)
\(=3\sqrt{2}-12\sqrt{2}+8\sqrt{2}-5\sqrt{2}\)
\(=-6\sqrt{2}\)
2) \(\sqrt{50}-\sqrt{18}+\sqrt{200}-\sqrt{162}\)
\(=5\sqrt{2}-3\sqrt{2}+10\sqrt{2}-9\sqrt{2}\)
\(=3\sqrt{2}\)
3) \(5\sqrt{5}+\sqrt{20}-3\sqrt{45}\)
\(=5\sqrt{5}+2\sqrt{5}-9\sqrt{5}\)
\(=-2\sqrt{5}\)
4) \(5\sqrt{48}-4\sqrt{27}-2\sqrt{75}+\sqrt{108}\)
\(=20\sqrt{3}-12\sqrt{3}-10\sqrt{3}+6\sqrt{3}\)
\(=4\sqrt{3}\)
5) \(\dfrac{1}{2}\sqrt{48}-2\sqrt{75}-\dfrac{\sqrt{33}}{\sqrt{11}}+5\sqrt{1\dfrac{1}{3}}\)
\(=2\sqrt{3}-10\sqrt{3}-\sqrt{3}+\dfrac{10}{3}\sqrt{3}\)
\(=-\dfrac{17}{3}\sqrt{3}\)
Ta có: \(75:\left(x+2\right)=5^3-\left(3^2+4^2\right)2^2\)
\(\Leftrightarrow75:\left(x+2\right)=25\)
\(\Leftrightarrow x+2=3\)
hay x=1
Giải:
a) \(75\%+1,2-2+\dfrac{1}{5}+2018^0\)
=\(\dfrac{3}{4}+\dfrac{6}{5}-2+\dfrac{1}{5}+1\)
=\(\left(\dfrac{6}{5}+\dfrac{1}{5}\right)+\left(\dfrac{3}{4}-2+1\right)\)
=\(\dfrac{7}{5}+\dfrac{-1}{4}\)
=\(\dfrac{23}{20}\)
b) \(\left(\dfrac{-4}{3}+0,75\right):\dfrac{2017}{2018}+\left(1+\dfrac{1}{3}-75\%\right):\dfrac{2017}{2018}\)
=\(\left(\dfrac{-4}{3}+0,75+1+\dfrac{1}{3}-75\%\right):\dfrac{2017}{2018}\)
=\(\left[\left(\dfrac{-4}{3}+1+\dfrac{1}{3}\right)+\left(0,75-75\%\right)\right]:\dfrac{2017}{2018}\)
=\(\left[0+0\right]:\dfrac{2017}{2018}\)
=0\(:\dfrac{2017}{2018}\)
=0
c)\(\left(2018-\dfrac{1}{3}-\dfrac{2}{4}-\dfrac{3}{5}-\dfrac{4}{6}-...-\dfrac{2018}{2020}\right):\left(\dfrac{1}{15}+\dfrac{1}{20}+\dfrac{1}{25}+\dfrac{1}{30}+...+\dfrac{1}{10100}\right)\)
=\(\left(1-\dfrac{1}{3}-1-\dfrac{2}{4}-1-\dfrac{3}{5}-1-\dfrac{4}{6}-...-1-\dfrac{2018}{2020}\right):\left(\dfrac{1}{15}+\dfrac{1}{20}+\dfrac{1}{25}+\dfrac{1}{30}+...+\dfrac{1}{10100}\right)\)
=\(\left(\dfrac{2}{3}-\dfrac{2}{4}-\dfrac{2}{5}-\dfrac{2}{6}-...-\dfrac{2}{2020}\right):\left(\dfrac{1}{15}+\dfrac{1}{20}+\dfrac{1}{25}+\dfrac{1}{30}+...+\dfrac{1}{10100}\right)\) =\(\left[2.\left(\dfrac{1}{3}-\dfrac{1}{4}-\dfrac{1}{5}-\dfrac{1}{6}-...-\dfrac{1}{2020}\right)\right]:\left(\dfrac{1}{15}+\dfrac{1}{20}+\dfrac{1}{25}+\dfrac{1}{30}+...+\dfrac{1}{10100}\right)\) =\(\left\{2.\left[\dfrac{5}{5}.\left(\dfrac{1}{3}-\dfrac{1}{4}-\dfrac{1}{5}-\dfrac{1}{6}-...-\dfrac{1}{2020}\right)\right]\right\}:\left(\dfrac{1}{15}+\dfrac{1}{20}+\dfrac{1}{25}+\dfrac{1}{30}+...+\dfrac{1}{10100}\right)\) =\(\left\{2.\left[5.\left(\dfrac{1}{15}-\dfrac{1}{20}-\dfrac{1}{25}-\dfrac{1}{30}-...-\dfrac{1}{10100}\right)\right]\right\}:\left(\dfrac{1}{15}+\dfrac{1}{20}+\dfrac{1}{25}+\dfrac{1}{30}+...+\dfrac{1}{10100}\right)\) =\(10.\left(\dfrac{1}{15}-\dfrac{1}{20}-\dfrac{1}{25}-\dfrac{1}{30}-...-\dfrac{1}{10100}\right):\left(\dfrac{1}{15}+\dfrac{1}{20}+\dfrac{1}{25}+\dfrac{1}{30}+...+\dfrac{1}{10100}\right)\) =-10
a) \(\frac{1}{2}x+\frac{3}{5}\left(x-2\right)=3\)
0,5 x + 0,6 ( x - 2 ) = 3
0,5 x + 0.6 x - 1,2 = 3
1,1 x = 4,2
x = \(\frac{42}{11}\)
Kết luận:
b) \(\frac{1}{3}x-0,5x=0,75\)
\(\frac{1}{3}x-\frac{1}{2}x=\frac{3}{4}\)
\(-\frac{1}{6}x=\frac{3}{4}\)
\(x=-\frac{9}{2}\)
Kết luận:
c) \(\frac{3}{-2}x-0,5x=75\%\)
-1,5x - 0,5x = 0,75
-2x = 0,75
x = -0,375
Kết luận:
d) \(-\frac{2}{5}x+\frac{1}{4}=75\%-\frac{3}{4}x\)
-0,4 x + 0,25 = 0,75 - 0,75 x
-0,4 x + 0,75 x = 0,75 - 0,25
0,35 x = 0,5
x = \(\frac{10}{7}\)
Kết luận:
\(a,\frac{1}{2}x+\frac{3}{5}\left(x-2\right)=3\)
\(\frac{1}{2}x+\frac{3}{5}x-\frac{6}{5}=3\)
\(\left(\frac{1}{2}+\frac{3}{5}\right)x-\frac{6}{5}=3\)
\(\frac{11}{10}x-\frac{6}{5}=3\)
\(\frac{11}{10}x=\frac{21}{5}\)
\(x=\frac{42}{11}\)
\(b,\frac{1}{3}x-\frac{1}{2}x=\frac{3}{4}\)
\(\left(\frac{1}{3}-\frac{1}{2}\right)x=\frac{3}{4}\)
\(\frac{-1}{6}x=\frac{3}{4}\)
\(x=\frac{-9}{2}\)
\(c,\frac{3}{-2}x-\frac{1}{2}x=75\%\)
\(\left(\frac{3}{-2}-\frac{1}{2}\right)x=\frac{3}{4}\)
\(-2x=\frac{3}{4}\)
\(x=\frac{-3}{8}\)
\(\frac{-2}{5}x+\frac{1}{4}=75\%-\frac{3}{4}x\)
\(\frac{-2}{5}x+\frac{3}{4}x=\frac{3}{4}-\frac{1}{4}\)
\(\left(\frac{-2}{5}+\frac{3}{4}\right)x=\frac{1}{2}\)
\(\frac{7}{20}x=\frac{1}{2}\)
\(x=\frac{10}{7}\)
`a)2sqrt{48}-4sqrt{27}+sqrt{75}+sqrt{12}`
`=8sqrt3-12sqrt3+5sqrt3+2sqrt3`
`=3sqrt3`
`b)sqrt{(3-sqrt5)^2}-sqrt{20}`
`=3-sqrt5-2sqrt5`
`=3-3sqrt5`
2 câu cuối không rõ đề :v
a: =25(15+45*3)
=25*150
=3750
b: \(=-10\left(25+75-50\right)=-10\cdot50=-500\)
c: =>3^x-2=27
=>x-2=3
=>x=5
d: =>2x-5=-4
=>2x=1
=>x=1/2
e: =>2(x-1)^2=32
=>(x-1)^2=16
=>x-1=4 hoặc x-1=-4
=>x=-3 hoặc x=5
f: =>25(x+3)=75
=>x+3=3
=>x=0
4.32 - 75:52
=4.9 - 75: 25
=36- 3
= 33
4.3^2-75:5^2=4.9-75:25=36-3=33